Análisis de las cadenas productivas en la provincia de Chimborazo y su incidencia en la generación de empleo – Caso Coprobich, periodo 2013 – 2014. - Quinchuela Andrade, José Luis (2017)
This research work focuses on an analysis of the value chains in the province of Chimborazo, the conceptualization, their environment and the priority sectors in different areas. Corporación de Productores, Comercializadores Organicos de Chimborazo (COPROBICH) describes the most representative chain actor in determining the impact on employment from the growth performance over the period of analysis. Chapter I includes the framework, statement with the approach and the formulation of the problem, the general and specific objectives of the research. Chapter II provides the theoretical framework through the theoretical foundation of the productive chains and employment details deductively with the current situation of the Province of Chimborazo in terms of production and socioeconomic development, the delimitation of the production chain of quinoa as part of referential research study, all of them constitutes the starting point through the problem is observed and at the same time they claim to be the evidence to judge, interpret and discuss the results. Chapter III contains the methodological framework, it means the analysis of the impact on employment generated for the development of the productive chain of COPROBICH, through the application of research tools, which show the results harmoniously synchronized, compared with theory and interpreted. It was tried to maximize the advantages of descriptive statistics to achieve greater understanding. Chapter IV outlines the conclusions that were reached upon completion of this research and recommendations are made with reference to the subject, which is expected to form the basis for future research in the provincial production.